Pendidikan Kesehatan Menggunakan Media Alat Peraga Dan Media Cerita Bergambar Terhadap Keterampilan Menggosok Gigi - Sainuddin; Abubakar, Syamsuddin; Saleh, Muhammad; Putri Candia, Hijrah; Supriatna, Agus (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Efforts in the field of dental health will contribute to improving the caliber and productivity of human resources as dental and oral health are essential to overall human health. Dental and oral health education (PKG) is a method of education that was developed in response to dental and oral health demands with the goals of raising living standards and promoting excellent dental and oral health. People acquire experience or information through a variety of instructional media during the educational process, which includes dentistry and oral health education. When the proper health education techniques and media are used, along with the involvement of additional senses, the outcomes will be ideal and the supply of health education will be more successful. The aim of this study was to determine the impact of oral health and dental education on children's proficiency in brushing their teeth at Al-Bayan Elementary School in Makassar City through the use of picture stories and visual aids. The pre-experimental design of this study employs a one-group pretest-posttest design, and simple random sampling is the sample method. The instruments utilized in this study were an observation sheet to measure teeth brushing abilities for the dependent variable and counseling utilizing media props and illustrated tale media for the independent variable. This study was analyzed using the Wilcoxon Sign Rank Test where the results of P value = 0.000 (p <0.05), which means that there is an effect of dental and oral health education using teaching aids and illustrated story media on teeth brushing skills in children at Integral Al-Bayan School Makassar City.